Governing the Transition from Groundwater Reliance to Sustainable Urban Water Services in Jakarta - Kurniasih Mufidayati (Universitas Muhammadiyah Jakarta, 2026)
Jakarta’s urban water crisis is not only a problem of infrastructure deficit but also a problem of governance transition. Despite ongoing efforts to expand piped water services, a substantial share of urban households continues to rely on groundwater, generating environmental risks, social inequality, and long-term threats to urban sustainability. This article examines how Jakarta governs the transition from groundwater dependence to sustainable urban water services through the lens of transformative governance. Drawing on a qualitative case study, the article analyzes policy documents, institutional arrangements, and stakeholder perspectives to assess five governance capacities: diversity, connectivity, polycentricity, redundancy, and directionality. The findings show that the transition is constrained by fragmented authority, uneven coordination across levels of government, limited integration between groundwater control and piped water expansion, and weak long-term strategic alignment. At the same time, emerging efforts in network expansion, regulatory reform, and institutional coordination indicate partial movement toward a more adaptive governance model. The article argues that sustainable urban water transition in Jakarta requires more than technical service delivery; it requires institutional reconfiguration, stronger cross-scale learning, and a clearer public direction toward water justice and resilience. By extending transformative governance to the study of urban water transitions in the Global South, this article contributes to debates on sustainability transitions, environmental governance, and equitable infrastructure transformation.